O010 Evaluating the Impact of COVID-19 Infection, Symptom Duration and Population Lockdown Measures on Sleep Quality and Mental Health. (9th November 2022) - Proctor, S; Cheetham, N; Toson, B; Bowyer, V; Banga, A; Brito, A; Leschziner, G; Joseph, D; Duncan, E; Mukherjee, S
Abstract: Background: The effect of COVID-19 (both acute and post-acute infection) and of lockdown on sleep quality and mental health are largely unknown. Methods: Between 9/2020 and 5/2021, the COVID Symptom Study Biobank recruited UK individuals with confirmed infection (symptom duration: asymptomatic, short [<2 weeks] or long [>4 weeks]); healthy uninfected controls, and uninfected individuals with short or long symptoms. Participants completed online sleep and mental health questionnaires at 9/2020 and 3/2021 (i.e., the equinoxes). Data were compared using one-way ANOVA, Chi-square and T-tests. Progress to date: 3053 participants completed questionnaires. Infected individuals with long symptom duration were younger (p<0.008) and more likely had prior mental illness (p<0.001). Long symptom duration was associated with poorer sleep quality (Pittsburgh Sleep Quality Index [PSQI], p<0.001, Sleep Condition Indicator [SCI], p<0.001) and increased sleepiness and fatigue (Epworth Sleepiness Scale [ESS], p<0.010, Chalder Fatigue Scale [CFS], p<0.001). In uninfected individuals, long symptom duration was also associated with prior mental illness (p<0.001), worse sleep quality (PSQI [p<0.001], SCI [p<0.001]), and increased sleepiness/fatigue (ESS p=0.010, CFS p<0.001). Independent of symptom duration, infected individuals were sleepier and more fatigued than uninfected individuals (mean±SD ESS 6.6±4.5 vs 6.1±4.1 [p<0.001], CFS 16±6.0 vs 14±4.9 [p<0.001]). Intended outcome and impact: Individuals with longer symptom duration (irrespective of infection) were more likely to have prior mental illness, with multiple markers of poor sleep and fatigue. Further analysis will determine the progression of sleep and mental health scores over time. Addressing these issues may help symptom management in individuals with long symptom duration.